The possibility using of Accounting Information in Rationalizing the Decisions of Capital Expenditure (A case study: Companies Listed in Khartoum Stock Exchange) - Mohammed Alhaj, Alfatih Alfadol (Journal of Economics and Administrative Sciences, 2020)
The research aims at the identity of the accounting information and its characteristics, and then to study the possibility of using accounting information in rationalizing the decisions of capital expenditure. The study relied upon the descriptive analytical approach it is suitable to the nature of this study, the hypotheses of the study were tested by using a number of statistical methods by relying on statistical package program (SPSS), and the research concluded that the companies listed in Khartoum Stock Exchange using accounting information in the comparison between investment alternatives available and estimating the number of years required to recover of the investment cost, the challenges that cause weakness in using the accounting information in rationalizing the decisions of capital expenditure: weakness of skills and the ability to deal with accounting information and its analysis. and the research recommends the providing all data and information that helps in rationalizing the decisions of capital expenditure, conducting more researches and studies that are concerned with studying the challenges to using accounting information in rationalizing the decisions of capital expenditure.